THE EFFECT OF PSYCHOLOGICAL CAPITAL AND ORGANIZATIONAL COMMITMENT IN RELATION TO JOB BURNOUT - Fadillah Ismail; Munirah Athirah Zaidi, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The idea of well-being, one of MADANI Malaysia's fundamentals, goes align with excellent health. Employee Wellness Report stated that 58% of Malaysian workers burnout and 51% report having a bad or average work-life balance. Job burnout has been associated with various adverse effects on the physical and mental health of employees. The purposes of this study are to investigate the level of psychological capital, organizational commitment, and job burnout among employees at Northport (Malaysia) Berhad. The purpose of this study also to identify and to determine the relationship and effect between psychological capital and organizational commitment towards job burnout among employee at Nothport (Malaysia) Berhad. The population for this research involves 443 employees at Northport (Malaysia) Berhad with 286 sample size. Sampling technique is a simple random sampling technique that researchers chose from the number of populations. This research methodology uses a quantitative survey approach with questionnaire is adopt and adapt from previous research, which is use PCQ instrument, OCQ instrument and MBI-GS instrument. The questionnaire is validated by experts and the reliability value is high. The results of this study on key issues related to job burnout of employees at Northport (Malaysia) Berhad. The finding of this research showed that the level of psychological capital is high, while level of the organizational commitment and job burnout level are moderate. In this study proved that a negative relationship between psychological capital and organizational commitment towards job burnout. However, there is a significant effect between organizational commitment and job burnout. This study aims to provide organizations with essential tools and insights to support and enhance employee work performance. Additionally, it strives to empower organizations to cultivate a workforce capable of making effective contributions towards the attainment of their broader corporate objectives.